DIRECTED READING THINKING ACTIVITY (DRTA) TECHNIQUES FOR IMPROVING TEACHING READING CLASS - Hartia Novianti (STKIP PGRI Jombang, 2015)
Direct Reading Thinking Activity (DRTA) is a strategy that explicitly teaches students good reading habits. This strategy helps strengthen reading and critical thinking skills. It can be used across all grades and learning abilities. The DRTA process helps students recognize predictions, judgments, and evidence verification. It is designed to make students aware of their own interprative action during reading. DRTA enhances understanding and comprehension of text. This strategy encourages students to be active and thoughtful readers and enhancing their comprehension. Keeping this need in mind, this paper reports on the implementation directed reading thinking activity (DRTA) of EFL learners in the first semester of English Department at STKIP PGRI Jombang. The result of observation showed sthat the steps on implementing DRTA are in the following (1) D-Direct- the lecturer directs and stimulates students thinking prior to reading a passage by scanning the title, chapter headings, illustrations, and other explanatory materials. (2)R- Reading – The lecturer should have students read up to the first preselected point in the text. The lecturer then prompts the students with questions about specific information or scanning. (3) T- Thinking, At the end of reading, the lecturer should have students go back through the text and think about their predictions. Students should verify or modify the accuracy of their predictions by finding supporting statements in the text. Moreover, the result of interview indicates that the students showed significantly positive attitude toward the implementation of DRTA.